1991
DOI: 10.1080/02701367.1991.10607515
|View full text |Cite
|
Sign up to set email alerts
|

Summary and Frequency of KR Presentation Effects on Retention of a Motor Skill

Abstract: This experiment investigates the recent proposal of Schmidt, Young, Swinnen, and Shapiro (1989) that summary knowledge of results (KR) improves skill retention. In Schmidt et al.'s experiment, however, summary length varied concomitantly with the frequency of KR presentation. The current investigation held KR presentation frequency constant while manipulating the number of trials seen in the summary KR display. Subjects were required to perform a timing task on a linear slide. Five groups (n = 12) of subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

1992
1992
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 11 publications
0
4
0
1
Order By: Relevance
“…learning) changes in performance, especially in motor learning. Sidaway B et al 23 ) reported that even though all their study groups improved with practice, the immediate KR group performed better than the other groups. John Liu & Craig A. Wrisberg 24 ) also concluded that KR is an effective method of feedback for improving the motor skills of the subjects.…”
Section: Discussionmentioning
confidence: 96%
“…learning) changes in performance, especially in motor learning. Sidaway B et al 23 ) reported that even though all their study groups improved with practice, the immediate KR group performed better than the other groups. John Liu & Craig A. Wrisberg 24 ) also concluded that KR is an effective method of feedback for improving the motor skills of the subjects.…”
Section: Discussionmentioning
confidence: 96%
“…Thus, both training groups showed a learning‐specific effect, relative to the control group. They were able to produce the acquired skill in the absence of feedback at immediate and delayed retention (12, 13). This result was partially in disagreement with previous findings on the effect of augmented visual feedback during manual dexterity training (6).…”
Section: Discussionmentioning
confidence: 99%
“…High KR presentation frequencies guide the learner during acquisition, resulting in poorer retention performance when compared to learners given a lower frequency of KR presentation during acquisition. 18 Researchers have tested the predictions of this KR guidance hypothesis in healthy subjects by reducing the frequency of KR during acquisition. These investigations have typically revealed beneficial learning effects of lower acquisition frequencies of KR.…”
Section: Introductionmentioning
confidence: 99%